Randomized controlled trial of 8 weeks' vs 12 weeks' interval between neoadjuvant chemoradiotherapy and surgery for locally advanced rectal cancer. (20th October 2019) - Terzi, C.; Bingul, M.; Arslan, N. C.; Ozturk, E.; Canda, A. E.; Isik, O.; Yilmazlar, T.; Obuz, F.; Birkay Gorken, I.; Kurt, M.; Unlu, M.; Ugras, N.; et al.
Abstract: Aim: The aim was to compare the pathological complete response (pCR) rate at 8 compared to 12 weeks' interval between completion of neoadjuvant chemoradiotherapy (CRT) and surgery in patients with locally advanced rectal cancer. Method: This was a randomized trial which included a total of 330 patients from two institutions. Patients with locally advanced (T3‐4N0M0, TxN+M0) rectal cancer were randomized into 8‐ and 12‐week interval groups. All the patients received long‐course CRT (45 Gy in 1.8 Gy fractions and concomitant oral capecitabine or 5‐fluorouracil infusion). Surgery was performed at either 8 or 12 weeks after CRT. The primary end‐point was pCR. Secondary end‐points were sphincter preservation, postoperative morbidity and mortality. Results: Two‐hundred and fifty‐two patients ( n = 125 in the 8‐week group, n = 127 in the 12‐week group) were included. Demographic and clinical characteristics were similar between groups. The overall pCR rate was 17.9% ( n = 45): 12% ( n = 15) in the 8‐week group and 23.6% ( n = 30) in the 12‐week group ( P = 0.021). Sphincter‐preserving surgery was performed in 107 (85.6%) patients which was significantly higher than the 94 (74%) patients in the 12‐week group ( P = 0.016). Postoperative mortality was seen in three (1.2%) patients overall and was not different between groups (1.6% in 8 weeks vs 0.8% in 12 weeks, P = 0.494). Groups were similar in anastomotic leak (10.8% in 8 weeks vs 4.5% in 12 weeks, P = 0.088) and morbidity (30.4% in 8 weeks and 20.1% in 12 weeks, P = 0.083). Conclusion: Extending the interval between CRT and surgery from 8 to 12 weeks resulted in a 2‐fold increase in pCR rate without any difference in mortality and morbidity.